Molecular characterization of the 3'-terminal region of Turnip mosaic virus isolates from astern China - Tian, Y.P.; Zhu, X.P.; Liu, J.L.; Yu, X.Q.; Du, J.; Kreuze, Jan F.; Li, X.D. (Wiley, 2007)
Turnip mosaic virus (TuMV; genus Potyvirus, family Potyviridae) causes great losses to cruciferous crop production worldwide. The 3'-terminal genomic sequences of eight TuMV isolates from eastern China were compared with those of 74 other Chinese TuMV isolates of known host origin in the GenBank and isolated during the past 25 years. The reported sequences of the eight TuMV isolates are 1125 or 1126-nucleotides (nt) long excluding the poly(A) tail. They all contain one partial open reading frame of 912 nt, encoding 304 amino acids, followed by a stop codon and a non-translated region of 209–210 nt. Results of phylogenetic analyses showed that Chinese TuMV isolates clustered into three groups: basal-BR, Asian-BR and world-B. The ratios of non-synonymous and synonymous substitutions and results of amino acid alignment provided evidence for purifying or negative selection in TuMV populations of China.